Soil characteristics and Cyperus spp. occurrence along a toposequence - Koné, B.; Touré, A.; Amadji, G.L.; Yao-Kouamé, A.; Angui, P.T.; Huat, J. (Wiley, 2013)
On acrisol (locally named terre de barre in Republic of Benin, West Africa), weed and soil (0–20 cm depth) were sampled at the beginning and the end of the cropping period in 2009 to gain knowledge about interaction between nutsedge occurrence and soil parameters. The samples were taken along a toposequence at the Africa Rice Center experimental station according to the topographic positions of summit, upper slope, middle slope and foot slope. At each topographic position, a 1 m × 1 m quadrat was set to study Cyperus abundance using 0, 3 and 5 abundance indices scale. Weed species sampled were identified, oven-dried and weighed. Soil particle sizes and organic C, total N, available P, K, Ca, Mg and extractable Fe contents were determined. Among the three species of Cyperus that were encountered, C. rotundus was the most frequent along the entire toposequence, while C. esculentus and C. sphacelatus were limited to the summit and upper slope, respectively. Sand, Fe and Pa contents of soil were influencing positively Cyperus spp. occurrence in opposition to C and Mg contents. But only the latest nutrients did so consistently and significantly. Thus, increasing organic matter and applying Mg fertilizer might enhance Cyperus control.